Hemogregarines in bufonid anurans from the Brazilian Amazon, with description a new species of Lankesterella (Apicomplexa: Lankesterellidae) - Alves-Coêlho, Tássio; Chagas-de-Souza, Darlison; Fernandes Chagas, Carolina Romeiro; Gutiérrez-Liberato, Germán Alfredo; Perles, Lívia [UNESP]; Alabi, Amir [UNESP]; André, Marcos Rogério [UNESP]; Viana, Lúcio André (Elsevier, 2025)
Here we describe, in an unprecedented way for the Brazilian Amazon, one Apicomplexa species infecting an anuran in Pará, Brazil, using an integrative approach that includes taxonomy, providing morphology, morphometrics, and molecular data. Samples were collected between February 2021 and February 2022 in the community of Curupira, municipality of Santarém, and in the industrial area of Marabá, both in Pará state. Specimens of Rhinella marina and Rhinella diptycha were captured by hand during the active search, and blood samples were collected by cardiac puncture. One blood aliquot was used to prepare blood smears for microscopical analysis and another aliquot for further molecular analyses. Of the five R. marina caught, one (20%) presented parasites morphologically compatible with the parasites belonging to the genus Hepatozoon, while of the three R. diptycha caught, one (33.3%) presented parasites morphologically compatible with the parasites belong to the genera Lankesterella and Hemolivia. Based on molecular data of 18S rDNA sequences, the Hepatozoon sequence obtained clustered with other parasite species recovered from Brazilian amphibians. The Lankesterella sp. sequence was placed in a sister clade of Lankesterella species described in birds and close to L. minima, described in amphibians. All attempts to amplify Hemolivia parasite DNA were unsuccessful. We described Lankesterella oliviacatarinae n. sp. and reported infection by Hepatozoon sp. and Hemolivia sp. in bufonids anurans from the Brazilian Amazon. This study increases knowledge of Brazilian anuran hemoparasites and confirms the importance of using an integrative approach for the taxonomy of these parasite groups.
Keywords: Amphibians; Haemococcids; Hemogregarines; Hemoparasites; Integrative taxonomy